2022
DOI: 10.1097/md.0000000000028768
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin and MMP-2 as potential biomarkers in the differential diagnosis of gestational trophoblastic diseases

Abstract: Background: Gestational trophoblastic diseases (GTDs) are characterized by vascular abnormalities of the trophoblast, but their pathogenesis is unknown. Angiogenin (ANG) and matrix metalloproteinase (MMP)-2, which are molecules implicated in the angiogenic process, may play some role in this process.Material and methods: We determined ANG and MMP-2 in the placental tissues of 26 patients who had a benign mole (BM), 12 patients with gestational trophoblast neoplasia (GTN) (1 invasive hydatidiform mole, 10 chori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 43 Another study reported elevated expression of MMP2 in the placental tissues and serum of gestational trophoblastic disease patients. 44 It is worthy of note that the MMP2 expression in tumor cells was only partially rescued by miR‐29c‐3p, which could be due to multiple mechanisms involved in MMP2 expression regulation. At the same time, MMP2 inhibition could not completely rescue the effects of miR‐29c‐3p inhibitors on cell invasion, suggesting additional targets of miR‐29c‐3p might play a role.…”
Section: Discussionmentioning
confidence: 97%
“… 43 Another study reported elevated expression of MMP2 in the placental tissues and serum of gestational trophoblastic disease patients. 44 It is worthy of note that the MMP2 expression in tumor cells was only partially rescued by miR‐29c‐3p, which could be due to multiple mechanisms involved in MMP2 expression regulation. At the same time, MMP2 inhibition could not completely rescue the effects of miR‐29c‐3p inhibitors on cell invasion, suggesting additional targets of miR‐29c‐3p might play a role.…”
Section: Discussionmentioning
confidence: 97%
“…7 Trophoblasts can produce MMPs, including MMP-2 (gelatinase A, 72 kDa) and MMP-9 (gelatinase B, 92 kDa), that degrade the uterine basement membrane. 16 Abnormal MMP-2 levels in placental tissues lead to choriocarcinoma progression by promoting tumor invasion and metastasis. Previous studies have demonstrated the ability of ATRA to inhibit MMP-2 in various tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…When such balance is disturbed, gestational trophoblastic diseases characterized by vascular abnormalities of the trophoblast may occur. 28 Angiogenin and matrix metalloproteinase-2, two important molecules during the angiogenic process, were significantly elevated in the placental tissues and maternal serum of patients with gestational trophoblastic diseases. A high level of placental growth factor has been reported to promote the development of blood vessels in choriocarcinomas.…”
Section: Update On Angiogenesis Mechanisms In Gynecological Cancersmentioning
confidence: 98%